2019
DOI: 10.1111/eje.12432
|View full text |Cite
|
Sign up to set email alerts
|

“I am a lefty in a right‐handed world”: Qualitative analysis of clinical learning experience of left‐handed undergraduate dental students

Abstract: Background: Left-handedness is the preferential use of the left hand in single-handed activities such as writing. There are many studies in the literature on left-handedness in relation to professional sports, medicine and surgery. Although dentistry largely depends on manual dexterity and hand skills, there has been little research to investigate the effect of left-handedness on clinical dentistry, particularly in Australasia. Aim:To gain an insight into the clinical learning experience of left-handed undergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
2
6
0
1
Order By: Relevance
“…In addition to the ergonomic designs of instruments and operating room set-up favoring right-handed use, this difference may reflect the fluidity of dexterity among left-handed people and the relatively rigid hand dominance of the right-handed population 7 . This finding echoes the experience of left-handed dental students, who were found to demonstrate “a very strong sense of adaptability” in a clinical setting that is oriented to right-handed practitioners 14 .…”
Section: Discussionsupporting
confidence: 75%
“…In addition to the ergonomic designs of instruments and operating room set-up favoring right-handed use, this difference may reflect the fluidity of dexterity among left-handed people and the relatively rigid hand dominance of the right-handed population 7 . This finding echoes the experience of left-handed dental students, who were found to demonstrate “a very strong sense of adaptability” in a clinical setting that is oriented to right-handed practitioners 14 .…”
Section: Discussionsupporting
confidence: 75%
“…However, their efficiency, effectiveness and level of confidence tend to improve as they progressed in their course. This situation was consistent with the findings by Al-Lawati et al (2019) that the left-handed dental students perceived their efficiency and level of confidence to their left-hand; the pseudo-left-handers who switched hands performing the dental procedures; and the transformed lefthanders who have adapted using their right-hand. Left-handed dental students face difficulties in adapting to right-handed dental instruments and performing certain dental procedures.…”
Section: Theme 4: Consequencessupporting
confidence: 90%
“…From the perspective of simulation dental training, it has been identified that left‐handed students may find the learning environment challenging due to lack of appropriately tailored educational resources 17 . For these reasons, a mirror image of resources in the form of PerioPal has been developed exactly to the same standards as for the right‐handed students.…”
Section: Discussionmentioning
confidence: 99%